CMR predictors of secondary moderate to severe mitral regurgitation and its additive prognostic role in previous myocardial infarction. Issue 1 (January 2022) - Di Bella, Gianluca; Pizzino, Fausto; Aquaro, Giovanni Donato; Bracco, Antonio; Manganaro, Roberta; Pasanisi, Emilio; Petersen, Christina; Zito, Concetta; Chubuchny, Vlad; Emdin, Michele; Khandheria, Bijoy K.; Carerj, Scipione; et al.
Abstract: Background: We aimed to determine predictors and the additive prognostic role of moderate to severe (MS) ischemic mitral regurgitation (MR) in myocardial infarction (MI). Methods: Four hundred twenty-two patients with previous MI underwent cardiac magnetic resonance (CMR) imaging for the assessment of left ventricular (LV) ejection fraction (EF), end-diastolic (EDV) and end-systolic volume (ESV), sphericity index, wall motion score index (WMSI), and late gadolinium enhancement (LGE). Echocardiography was performed to assess MR. Results: Thirty-eight had from moderate to severe MR (MS-MR group) and 384 did not (No MS-MR group). The S-MR group had higher LV volumes, sphericity index, WMSI, and LGE extent, and lower LVEF. At univariate logistic regression analysis, dilated volumes, SI >0.43, dyskinesia of inferolateral wall, papillary muscle (PM)-LGE, and LGE extent >16% were associated with MS-MR. At multivariate analysis, only SI (OR=5.7) and PM-LGE (OR=3) were independently associated with MS-MR. Considering only patients without LV dilatation, only dyskinesia in the inferolateral wall was a predictor of MS-MR (OR 34.8). Thirty cardiac events (cardiac death, appropriate implantable cardioverter-defibrillator firing, and resuscitated cardiac arrest) occurred during a median follow-up of 1, 276 days. After adjusting the prognostic variables at univariate analysis by age (>65 years) and selecting those that were significant (EDV > 95 ml/m 2, ESV >53 ml/m 2, EF <30%, WMSI >1.65, LGE >12%, S-MR), only WMSI >1.65 and MS-MR remained an independent predictor of cardiac events. Conclusions: Increased WMSI and PM-LGE in the overall population and inferolateral dyskinesia in patients without ESV dilatation are predictors of MS-MR; MS-MR and elevated WMSI have independent negative prognostic value. Highlights: Left ventricular (LV) dilatation and scar tissue in papillary muscle are associated with severe mitral regurgitation (MR) Inferolateral dyskinesia is predictor of severe MR in the absence of LV dilatation Severe MR and wall motion abnormalities are strong independent predictors of death Graphical abstract: Moderate/severe mitral regurgitation alone (A) and adjusted for wall motion score index (WMSI) >1.65 (B) are associated with a worse prognosis. Late gadolinium enhancement in papillary muscle (particularly posteromedial papillary muscle, red arrow in Panel C) is independently associated with moderate/severe mitral regurgitation. Image, graphical abstract